Alcmaeon of Croton, On Nature (Περὶ φύσεως). Main Doxography and Fragments - Wesoły, Marian Andrzej (Sensus Historiae, 2023)
Alcmaeon of Croton (sixth-fifth century BC) was an early Greek physician–philosopher and medical theorist of considerable originality, the author of the lost writing Peri physeos. He was most concerned with explaining the psychology and physiology of living beings, the definition of health and disease. After a general introduction, we give in the new Polish translation the most important ancient testimonies about Alkmaeon, in some possibly systematizing order, according to thematic headings, without dissecting the texts in their doxographic compactness, and we give his few verbatim fragmenta in bold print, together with the given context of the authors who selectively quoted them.